Livelihood Improvement through Hybrid Vegetable Cultivation - Mathur, I. J.; Intodia, S. K.; Agarwal, S. K. (Indian Farming, 2015)
There are a number of tribal households in the South Rajasthanregion which have benefitted because of the livelihood securityinterventions introduced under NAIP. Initiative has been taken toimprove and ensure livelihood of small and marginal farmers of tribal dominated areas through diversification of existing croppingsystem with high value crops.